2009
DOI: 10.1016/j.actbio.2008.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of erodible, DNA-containing thin films on the surfaces of polymer microparticles: Toward a layer-by-layer approach to the delivery of DNA to antigen-presenting cells

Abstract: We report a layer-by-layer approach to the assembly of ultrathin and erodible DNA-containing films on the surfaces of polymer microparticles. DNA-containing multilayered films were fabricated layerby-layer on the surfaces of polystyrene microspheres (~6 μm) by iterative and alternating cycles of particle suspension, centrifugation, and resuspension in solutions of plasmid DNA and a hydrolytically degradable polyamine. Film growth occurred in a stepwise manner, as demonstrated by characterization of the zeta po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 68 publications
(85 reference statements)
5
45
0
Order By: Relevance
“…A promising system for biomedical applications is based on colloidal capsules prepared by the layer-by-layer (LbL) adsorption of polymers onto sacrificial template particles [14,15]. This method provides control over the size of the capsules (from tens of nanometres [16][17][18] to several microns [19]), allows the use of biocompatible [20] and biodegradable [20,21] polymeric building blocks, and enables the engineering of capsules to respond to temperature [22], light [23][24][25] and pH [26]. Recent reports of LbLassembled capsules have demonstrated their utility in applications ranging from drug delivery [27], targeting [28] and sensing [29,30] to the creation of microreactors [31,32] and artificial cells [33].…”
Section: Introductionmentioning
confidence: 99%
“…A promising system for biomedical applications is based on colloidal capsules prepared by the layer-by-layer (LbL) adsorption of polymers onto sacrificial template particles [14,15]. This method provides control over the size of the capsules (from tens of nanometres [16][17][18] to several microns [19]), allows the use of biocompatible [20] and biodegradable [20,21] polymeric building blocks, and enables the engineering of capsules to respond to temperature [22], light [23][24][25] and pH [26]. Recent reports of LbLassembled capsules have demonstrated their utility in applications ranging from drug delivery [27], targeting [28] and sensing [29,30] to the creation of microreactors [31,32] and artificial cells [33].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of cationic species could result in unwanted toxicity especially when administered in multiple doses. To overcome the release problem of siRNA, polymers have been designed to incorporate side chain molecules that trigger a release when stimulated using temperature 23 , pH 24 , redox potential 25,26 , light 27 , electrical pulse 28,29 and enzymatic degradation 30,31 . Such release mechanisms rely on either external (remote) or environmental stimuli.…”
mentioning
confidence: 99%
“…Due to the inherent properties of DNA as a natural biological compound, multilayers containing DNA have been investigated for their possibility of providing relatively low-immunogenic coatings [3] and surface-mediated cell transfection on various substrates [4][5][6][7]. Multilayers containing a top DNA layer have shown a significant increase in primary rat dermal fibroblast proliferation as compared to non-coated glass surfaces in vitro, while in vivo tissue response studies also showed that the DNA-coatings are histocompatible without showing signs of inflammation or adverse reactions [3].…”
Section: Introductionmentioning
confidence: 99%